The Phylogeny of Prokaryotes Associated with Australia's Great Basin - Spanevello, Mark (Griffith University, 2001)
The Great Artesian Basin of Australia is the largest freshwater artesian basin in the world. It underlies arid and semi-arid regions of Queensland, New south Wales, South Australia and the Northern territory, approximately 20% of the Australian continent. Temperatures of its' waters range from 30°C to over 100°C and over 5000 bores access its waters and empty into open drainage systems for agricultural irrigation and stock watering purposes. The Great Artesian Basin of Australia has great economic and agricultural importance, but prokaryotic communities persisting in the bore waters influence its' quality. To gain an understanding of these prokaryotic communities, a culture-independent study was conducted on microbial communities present in the outflow of the New Lorne bore (registered bore number 17263). Five distinct prokaryotic communities existing at different temperatures (88°C, 75°C, 66°C, 57°C, and 52°C) were selected and total genomic DNA was extracted. PCR-amplified 16S rRNA genes were subsequently cloned and a total of 64 clones from the 88°C community and 96 clones from the other communities were examined. Partial sequences identified phylotypes that were then fully sequenced and analysed phylogenetically. The analysis revealed identical phylotypes existing in adjacent communities, as well as an increase in the phylogenetic diversity as water temperature decreased. Sequences identified belonged to species spanning the full diversity of the Bacterial domain, including Hydrogenobacter, Thermus, Meiothermus, Chloroflexus, Cytophaga, Planctomycetes, Rhodothermus, Bacillus, Clostridium, Nitrospira, Verrucomicrobium, Acidobacterium, Î±-, Î²-, Î³-, and Î´-Proteobacteria. Clones recovered also grouped with taxa with no isolated representatives. Of the libraries, 24 phylotypes from 6 phyla had a similarity of 96% or more to cultured isolates and comprised 73% of all clones analysed. 34 phylotypes from 11 phyla had less than 96% similarity to cultured isolates, or were related to previously cloned 16S rRNA gene sequences, and comprised 27% of the clones analysed. This shows the prokaryotic ecology of the Great Artesian Basin environment includes a diverse range of many uncultured, novel species. Previous studies on isolates of Thermus and Meiothermus have revealed a relationship between the taxonomic groups and the geographical sites of isolation. A survey of 14 Thermus and 2 Meiothermus isolates and 16S rRNA gene clone data from the New Lorne bore extends the geographical diversity of these two genera. Thermus was isolated from all four mat samples and were most dominant in the red mat at 66°C. Meiothermus was only isolated from the red mat at 66°C. 16S rRNA gene sequence analysis revealed that 13 of the 14 Thermus isolates were closely related to T. igniterrae (100% similarity) and one isolate was closely related to Thermus strain SRI-96 (99.1% similarity). Both Meiothermus had 100% similarity with Meiothermus ruber. The 16S rRNA gene study of the environment showed that Thermus dominated the grey mat (75°C) followed by the red mat (66°C) and green mat (57°C), but was absent from the brown mat (52°C). Four Thermus phylotypes were identified with T. scotoductus the most dominant, followed by T. igniterrae, Thermus strain SRI-248, and T. oshimai. T. scotoductus dominated over T. igniterrae in the grey mat library, and, only marginally, in the red mat. Phylotypes belonging to the genus Meiothermus were identified in the red, green and brown mats, but not in the grey coloured mats with 2 distinct phylotypes related to M. ruber and M. cerberus. The M. ruber phylotype was dominant in the red mat and the M. cerberus phylotype was dominant in the brown mat with M. ruber only slightly dominant over M. cerberus in the green mat. Based on 16S rRNA gene sequence analysis, isolates and clones were most similar to those obtained from hot springs in Iceland, perhaps demonstrating a ecological similarity between the Great Artesian Basin of Australia and Iceland's thermal environments. Similarity of biodiversity was low between Thermus and Meiothermus species identified from the Great Artesian Basin and other well-studied thermal environments such as Yellowstone National Park, USA and New Zealand. From enrichment studies, a strictly aerobic, thermophilic, Gram-positive, spore-producing rod-shaped bacterium (2 - 10Î¼m x 0.3Î¼m), designated isolate C21T (T = type strain) was isolated from a sediment sample collected from the run-off channel of the New Lorne bore accessing the Great Artesian Basin of Australia. Isolate C21T grew optimally at 70°C (temperature range for growth between of 55°C and 80°C) and a pH of 8.5 (pH growth range between 6 and 10.5) with a generation time of 90 minutes. The isolate is strictly heterotrophic and grew on yeast extract and/or tryptone as sole carbon and energy source(s). The growth of isolate C21T was not improved with the addition of a variety of carbohydrates (sucrose, cellobiose, glucose, dextrin, amylopectin, chitin, xylan, carboxymethylcellulose, inositol, arabinose, mannose, fructose, gelatin, starch, amylose, galactose, dextrose, xylose, maltose, L-sorbose, and raffinose), organic acids (lactic acid, pyruvic acid, and benzoic acid), or casamino acids without either yeast extract or tryptone. The G+C content of the chromosomal DNA of isolate C21T was 71mol%. A phylogenetic analysis of the 16S rRNA gene of isolate C21T indicated that it was a member of the phylum Firmicutes clustering with Thermaerobacter marianensis (similarity of 98%). However, isolate C21T differed from T. marianensis in a number of key physiological and phenotypic properties and based on the evidence isolate C21T is designated Thermaerobacter subterranea sp. nov. (type strain C21T = ATCC BAA-137). To further understand the prokaryotic ecology of the Great Artesian Basin, the development of real-time PCR to detect and quantify environmental isolates of Caloramator was undertaken. Thermophilic isolates from the genus Caloramator within the phylum Firmicutes are readily isolated from drainage systems of the Great Artesian Basin of Australia. Adjacent hybridisation probes were designed to identify Caloramator strains. The real-time PCR was optimised by manipulating the PCR and the concentrations of the adjacent hybridisation probes. Real-time PCR enabled the detection of as little as 6fg of DNA in the 45 PCR cycles. The development of real-time PCR will provide the foundation of applying this technique to identify and monitor other, perhaps detrimental, members of prokaryotic communities in the environment. The information provided by the examination of these communities has improved our understanding of the culturable and non-culturable members of the prokaryotic communities of the Great Artesian Basin of Australia and provides the basis for further ecological studies of the Great Artesian Basin.